Waste Management Planning in Amirkabir Petrochemical Complex - Maryam Abbasi; Hamid Reza Kamalan (Environmental Energy and Economic Research, 2018)
The Amirkabir petrochemical complex (APC) is located in the south of Iran, on the northern coastline of the Persian Gulf. It has five different units which generate various waste estimated at 3115.98 ton/year. The objective of this study was to focus on the management of the processing wastes for minimizing the adverse environmental impacts. In order to properly manage and control waste generation at APC, the quantity, type, and composition of industrial wastes must be known. Therefore, questionnaires were used to collect data. Classification of industrial wastes was carried out based on a comparative analysis and synthesis of studies pertaining to petrochemical waste management. Whereby unique coding system is essential for integrated management of industrial waste, a thirteen-digit code was assigned for each waste. The main types of waste were 9.58% catalysts, 7.62% metallic materials, 35.77% plastic barrel, 12.66% coke, 4.47 % wood, 4.15% oil, 0.028 % glass, 6.7% cooling tower packing and 18.83% other material. Physical properties analysis of the wastes showed that 11.81% of these residues were liquid and 88.19% were solids. Serious problems were encountered in the present management of these wastes. The waste management at APC was quite complicated because of the diversity of wastes and their hazardous characteristics (88.19% hazardous waste). In some cases, recycling/reuse of waste was the best option, but incineration and disposal are also essential choices.